Analisis Faktor – Faktor Yang Mempengaruhi Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Masyitah Fujianugrah MM (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2019)
ABSTRACT The object of this research is all manufacturing companies listed in Indonesia Stock Exchange 2010-2014, as many as 150 companies. Samples were selected using purposive sampling. The number of samples in this study were as many as 16 companies. The collection of data by accessing internet sites to the Indonesia Stock Exchange. The analytical method used is multiple linear analysis. The results of this study show that: Simultaneously, the factors that consists of a variable Dividend, Profitability, Sales Growth, Stock Return simultaneously significant effect on stock prices. Partially, Profitability and Sales Growth variables significantly influence stock prices while variable Cash Dividend and Stock Return no significant effect on stock prices Keywords :Cash Dividend, profitability (ROA), Sales Growth, Return on Equity, Stock Price